Revitalizing from ashes: Economic development and business resilience in the City of Vukovar - Jakša Puljiz; Marina Funduk; Ivana Biondić (Economies, 2023)
The paper examines a paradigmatic example of post-conflict economic development of Vukovar, Croatia. It represents a pertinent case study for localities encountering analogous challenges, most notably urban areas in Ukraine in the near future. The war that broke out in 1991 brought significant human casualties, population displacement, and extensive destruction of residential, social, and economic infrastructure. The completion of the peaceful reintegration of Vukovar into Croatia's legal system in 1998 marked the beginning of the socio-economic revitalization process. The research scrutinizes the primary impediments and prospects for Vukovar's economic growth, probing why substantial investments in reconstructing housing, transport, communal infrastructure, and fiscal incentives for businesses have not paralleled its economic performance. It concentrates on the local business climate and influential factors as potential explanations for this discrepancy. The topic was designed as a case study and was covered by document analysis, survey method, and semi-structured interviews. Utilizing a mixed-methods approach, the study collates perspectives from entrepreneurs and business support institutions. The results confirmed that reconstruction of housing and social infrastructure is necessary, but more conditions are needed for successful post-conflict economic development, and that the business climate in lagging local units highly depends on state- and locally designed business-support measures.
Keywords: 330; local economic development; post-conflict reconstruction; regional development; City ofVukovar; entrepreneurs